Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/en10122021
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Structure of the Straight Cone Nozzle and the Parameters of Borehole Hydraulic Mining for Huadian Oil Shale Based on Experimental Research

Abstract: Abstract:Oil shale is a kind of potential alternative energy source for petroleum and has attracted the attention of energy researchers all over the world. Borehole hydraulic mining has more prominent advantages than both conventional open-pit mining and underground mining. It is very important to attempt to use the borehole hydraulic mining method to exploit underground oil shale. The nozzle is the key component of borehole hydraulic mining and reasonable mining parameters are also crucial in exploiting under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 7 publications
(7 reference statements)
0
25
0
Order By: Relevance
“…In the practice, the straight cone nozzle is the most commonly used for HPJG, as shown in Figure 1 and Figure 2. The straight cone nozzle mainly consists of three parts: connection section, contraction section, outlet section [11][12]. For the normal nozzle, the all of the internal surfaces are smooth.…”
Section: Structures Of Nozzles For Hpjgmentioning
confidence: 99%
“…In the practice, the straight cone nozzle is the most commonly used for HPJG, as shown in Figure 1 and Figure 2. The straight cone nozzle mainly consists of three parts: connection section, contraction section, outlet section [11][12]. For the normal nozzle, the all of the internal surfaces are smooth.…”
Section: Structures Of Nozzles For Hpjgmentioning
confidence: 99%
“…There are many types of nozzle that can produce the direct water jet such as: the straight cone nozzle, conical nozzle, arc inlet nozzle, elliptical inlet nozzle, etc. However, based on comprehensive considerations such as: machining processes, working efficiency, applicability condition, and costs; it is concluded that the best and the most widely used nozzle is the straight cone nozzle [ 14 , 18 – 25 ].…”
Section: Theories Of High Pressure Water Jetmentioning
confidence: 99%
“…As mentioned above, the most critical step in the entire borehole hydraulic mining process is breaking the underground oil shale by the high-pressure water jet produced by the jet device. The outcome of this step will directly determine the success and efficiency of the mining process [ 14 – 18 ]. Additionally, in this study, the straight-cone nozzle, self-resonating cavitating jet nozzle, and self-excited oscillation pulsed jet nozzle are collectively referred to as the jet devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taherdangkoo et al [4] proposed a new predicting scheme to evaluate bottomhole circulating pressure in petroleum industry and this method was able to predict the complex relationship between inputs and outputs of a highly nonlinear system. Wen et al [5] comprehensively analyzed the results of an orthogonal experimental design and demonstrated the optimal structural parameters of a straight cone nozzle. Ge et al [6] proposed a novel method that used a self-propelled water-jet nozzle to dredge blocked boreholes in coal seams in order to improve the coal bed methane output and coal mine safety.…”
Section: Introductionmentioning
confidence: 99%